Body mass index, abdominal fatness and pancreatic cancer risk: a systematic review and non-linear dose–response meta-analysis of prospective studies - Aune, D.; Greenwood, D.C.; Chan, D.S.M.; Vieira, R.; Vieira, A.R.; Navarro Rosenblatt, D.A.; Cade, J.E.; Burley, V.J.; Norat, T. (Annals of oncology, 2012)
Questions remain about the shape of the dose–response relationship between body mass index (BMI) and pancreatic cancer risk, possible confounding by smoking, and differences by gender or geographic location. Whether abdominal obesity increases risk is unclear. We conducted a systematic review and meta-analysis of prospective studies of the association between BMI, abdominal fatness and pancreatic cancer risk and searched PubMed and several other databases up to January 2011. Summary relative risks (RRs) were calculated using a random-effects model. Twenty-three prospective studies of BMI and pancreatic cancer risk with 9504 cases were included. The summary RR for a 5-unit increment was 1.10 [95% confidence interval (CI) 1.07–1.14, I2 = 19%] and results were similar when stratified by gender and geographic location. There was evidence of a non-linear association, Pnon-linearity = 0.005; however, among nonsmokers, there was increased risk even within the ‘normal’ BMI range. The summary RR for a 10-cm increase in waist circumference was 1.11 (95% CI 1.05–1.18, I2 = 0%) and for a 0.1-unit increment in waist-to-hip ratio was 1.19 (95% CI 1.09–1.31, I2 = 11%). Both general and abdominal fatness increases pancreatic cancer risk. Among nonsmokers, risk increases even among persons within the normal BMI range.